Pictorial Appearing : Image Theory After Representation. - Purgar, Kresimir (Image., 2018)
The proliferation of digital technology has changed our visual perception and the way we interpret terms such as 'representation', 'immersion', and 'virtuality'.0Kresimir Purgar examines some of the topics fundamental to an understanding of the contemporary culture of images. The principal thesis of this volume is that we are witnessing the transitional period of images as not-representation-anymore and not-yet-immersion. Instead of just asking what images mean, we should ask ourselves what images are, how they appear, and what they do to us. The author proposes the comprehensive concept of "pictorial appearing" that takes into account phenomenological, semiotic, and art-historical perspectives on both old and new images.